Energy Efficiency of Substation Buildings Based on Low Power Analysis Technology - Jingbo Song; Chen Chen; Liang Zhang; Han Yao; Kai Li; Jinfeng Zhang (IEEE Access, 2025)
To promote environmentally friendly and low-carbon growth of buildings, accelerate building energy efficiency renovation, and solve the substation energy consumption problem, the study proposes to analyse substation buildings with wireless sensor network low power technology. The study starts from three parts: building loss analysis, energy consumption simulation model building and single factor method design. It is also verified with the help of simulation software and orthogonal tests, taking into account the characteristics of energy consumption of substation buildings. The results show that the improved scheme proposed in this study is effective in analyzing the energy consumption of the equipment with a minimum success rate of more than 0.7. The average resource loss and the average delay are significantly better than the other protocols, and the maximum resource loss for the optimised substation construction is reduced by more than 15%. As the value of the roof heat transfer coefficient increases, it leads to a change in the unit air conditioning energy consumption of more than 9 kW.h/m2. the minimum annual cumulative cooling load value of 484.024 W.h/m2 is achieved when its value is 1.0. factors such as the building orientation, the indoor temperature setting, and the ratio of the window and wall area all have an effect on the building energy consumption. The research results can promote efficient energy-saving management of substation construction and sustainable development of power systems.